2012
DOI: 10.1016/j.tet.2012.05.094
|View full text |Cite
|
Sign up to set email alerts
|

Concise approach to 1,4-dioxygenated xanthones via novel application of the Moore rearrangement

Abstract: The rapid synthesis of 1,4-dioxygenated xanthones and related natural products employing the Moore rearrangement as a key transformation has been developed. The approach features an acetylide stitching step to unite a substituted squaric acid with a protected hydroxy benzaldehyde derivative to provide a key intermediate that undergoes facile Moore rearrangement to deliver a hydroxymethyl aryl quinone. Subsequent oxidation, hydroxy group deprotection and cyclization then affords highly functionalized xanthones.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…When the cyclobutenol 23 was heated, a simple Moore rearrangement occurred to give 24 . 10,11 The putative acetylenic vinyl ketene intermediate did not undergo the desired cyclization as expected from the work of Fuganti 15 under any of the conditions examined.…”
Section: The First Generation Approachsupporting
confidence: 54%
See 3 more Smart Citations
“…When the cyclobutenol 23 was heated, a simple Moore rearrangement occurred to give 24 . 10,11 The putative acetylenic vinyl ketene intermediate did not undergo the desired cyclization as expected from the work of Fuganti 15 under any of the conditions examined.…”
Section: The First Generation Approachsupporting
confidence: 54%
“…The regiochemical outcome of the cyclization to form the spirocyclic ring system in 26 rather than the desired 1,4-dioxygenated xanthone ring in 27 was consistent with previous observations from our laboratory in which we found that the substitution pattern on the F-ring of 25 governs the regioselectivity of cylization. 11 Microwave heating of 25 resulted in rearrangement of the spirocycle to the thermodynamically favored xanthone, and an aqueous base work-up resulted in oxidation of the hydroquinone intermediate and isolation of quinone 27 in quantitative yield. Although our initially proposed reaction sequence for forming xanthones directly from cyclobutenones was unsuccessful, we devised an alternative approach that allowed us to effectively convert cyclobutenedione 22 into xanthone 27 in only five steps.…”
Section: The First Generation Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Such compounds range in structural complexity from the tricyclic tetramethoxyxanthone 43 to the polycyclic representatives IB-00208, 44 citreamicin η, 45 and kibdelone C (Figure 5, xanthone rings highlighted in blue). Many compounds of this class exhibit potent antibacterial and anticancer activity.…”
Section: General Route To Polycyclic Xanthone Natural Productsmentioning
confidence: 99%